Patient-Centric Structural Determinants of Adherence Rates Among Asthma Populations: Exploring the Potential of Patient Activation and Encouragement Tool TRUSTR to Improve Adherence - Asim Zia; Arthur Brassart; Sheila Thomas; Fen Ye; Judith J. Stephenson; C. Daniel Mullins; Christopher A. Jones (Journal of Health Economics and Outcomes Research, 2020)
# Background Lack of adherence with prescribed medications among the asthma populations exacerbates health outcomes and increases social and economic costs.